INVESTIGATION OF THE RADIOPROTECTIVE EFFECT OF ORTHOVANADATE IN MICE AFTER TOTAL BODY IRRADIATION - Šinkorová, Zuzana; Filipová, Alžběta; Vávrová, Jiřina; Pejchal, Jaroslav; Andrejsová, Lenka; Jeličová, Marcela; Marek, Jan; Havelek, Radim; Seifrtová, Martina; Řezáčová, Martina; Tichý, Aleš (Radiation protection dosimetry, 2019)
The increasing risk of acute large-scale exposure of ionising irradiation on the population underlines the necessity of developing effective radioprotective and mitigating agents. The aim of this work was to investigate the effect of sodium orthovanadate pre-treatment on mice exposed to high doses of gamma rays (from 5 to 13 Gy). The determination of median lethal dose within 30 days confirmed that orthovanadate applied to total-body-irradiated mice intra-peritoneally has a radioprotective but not a mitigating effect. With orthovanadate pre-treatment, the composition of cellularity in the bone marrow improved substantially and the main lymphocyte populations restored during the first month after irradiation. These findings contribute to 'gap-filling' in radioprotective effects and demonstrate the importance of haematological parameters in radiation-response prediction.
Keywords: vanadáty; Bone Marrow; Lymphocytes; lymfocyty; T-Lymphocytes; ionizující záření; radioprotektivní látky; nádorový supresorový protein p53; Radiation, Ionizing; makrofágy; Radiation-Protective Agents; zvířata; myši; myši inbrední C57BL; Whole-Body Irradiation; B-lymfocyty; buňky NK; Mice; Killer Cells, Natural; Cyclin-Dependent Kinase Inhibitor p21; Flow Cytometry; celotělové ozáření; B-Lymphocytes; kostní dřeň; Mice, Inbred C57BL; Vanadates; průtoková cytometrie; T-lymfocyty; Animals; Macrophages; inhibitor p21 cyklin-dependentní kinasy; Tumor Suppressor Protein p53